Birth : three mothers, nine months, and pregnancy in America - Grant, Rebecca (Journalist) (Avid Reader Press, 2023)
Follows three first-time mothers as they experience pregnancy and giving birth in modern America, recounting the ups and downs, fears, joys and everyday moments of each woman's pregnancy and postpartum journey and discussing the rising popularity of midwifery.